Strategi Pembelajaran Berbasis Teknologi Digital pada SD/MI: Analisis Systematic Literature Review terhadap Model dan Medianya - Rizkiatul Nadila; Anita Khusna Manzila; Chandra Widya Kesumadyaningtyas; Fitriyani; Nurlaila Ana (FingeR: Journal of Elementary School, 2026)
This study aims to analyze digital technology-based learning strategies at the Elementary School/Islamic Elementary School (SD/MI) level trough a Systematic Literature Review (SLR) approach. The background of this research is based on the rapid development of digital technology in the Industrial Revolution 4.0 era and the need for interactive, innovative, and student-centered learning. Data were collected through searching scientific articles in various databases such as Google Scholar, Garuda, and national and international journals spanning the years 2020-2025. The analysis process was carried out through the stages of identification, selection, evaluation, and synthesis of article content. The result show that digital technology-based learning strategies, such as blended learning, hybrid learning, and flipped classroom, have proven effective increasing student motivation, engagement, and learning outcomes. The most widely used media include Canva, learning videos, digital platforms (Google Classroom and Zoom), and Augmented Reality (AR) technology. However, in the implementation of digital learning still faces obstacles such as limited infrastructure, internet acces, and teachers digital competencies. Therefore, infrastructure support and teacher capacity building are needed so that the use of digital technology in learning can run optimally and sustainably.